Bruno Latour’s Theo-Ecologies and Eco-Theologies, or on the Pedagogical Potential of a Hybrid Language as an Inspiration for a Religious studies Pedagogy of Religion - Humeniuk, Monika (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2022)
We live in an age of planetary instability. The climate crisis has effectively captured the public imagination. It seems that in the face of numerous environmental crises, even science and religion, despite all their irremediable differences and mutual biases, are sometimes able to think and act together. The interpenetration of these two distinct orders: ‘knowledge’ and ‘faith’ is a symptom of such a change. The example of Bruno Latour’s ecotheological argument presented in this study is an interesting testimony to the hybridization of the language of science and the language of religion. Since Latour’s ‘negotiations’touch upon such unobvious interfaces as STS and humanities or science and religion, it is worthwhile for the pedagogy of religion to reach not only to theology, which is a constant point of reference for the traditional pedagogy of religion, but also to critical religious studies. Its theoretical potential could help integrate the topic of religion withnew-materialist, post-secular, non-anthropocentric, post-humanist, and pro-ecological thought.
Keywords: Bruno Latour; Anthropocene; science; religion; hybridity; hybridization; pedagogy of religion